Liturgy in the Broadest Sense - Lloyd, Vincent (New blackfriars, 2011)
Theologians interested in postmodernism and contemporary culture have recently turned to liturgy as a resource. However, these scholars often overlook the rich tradition of philosophically and theologically sophisticated reflection on liturgy of the past few decades. The result is that essential features of liturgy are overlooked. These features include the authoritative nature of liturgy for theology, and the impossibility of fully expressing the content of liturgy in propositional theology. By turning to the work of liturgical theologians, including Alexander Schmemann, Aidan Kavanagh, and Geoffrey Wainwright, I suggest that the attempt to grapple with contemporary issues by appealing to liturgy will always be compromised unless liturgy is understood in a modest, not broad, sense. I argue that recent work by Catherine Pickstock and William Cavanaugh, among others, ignores the authoritative nature of liturgy. These recent enthusiasts of liturgy promote a ‘liturgical culture’, but in the process their work takes away what makes liturgy most potent.